Experimental Evaluation and Performance Analysis of a Dual-Factor IoT-Based Smart Door Security System - Mira, Anwar (Yayasan Kita Menulis, 2026)
This research presents the design, implementation, and experimental evaluation of an Internet of Things (IoT)-enabled smart door security system integrating biometric and PIN-based authentication. The study benchmarks system performance through quantitative metrics including authentication accuracy, latency, and wireless communication stability. Unlike prior single-factor systems, the proposed dual-factor model demonstrates improved resistance to unauthorized access and enhanced reliability under varied environmental conditions. Comparative analysis with traditional and commercial smart locks reveals that the developed system achieves faster response times (<2 s), higher authentication accuracy (98.5%), and lower cost while maintaining user convenience. The findings contribute an empirically validated framework for secure, modular, and cost-efficient IoT-based access control.